Педагогічні умови розвитку творчого потенціалу магістрів дошкільної освіти у процесі професійної підготовки - Ємчик, Олександра; Iemchyk, Aleksandra (My University, 2016)
У статті виокремлено та проаналізовано педагогічні умови розвитку творчого потенціалу магістрів дошкільної освіти у процесі професійної підготовки. Визначено поняття педагогічних умов та важливість їх реалізації для підвищення ефективності професійної підготовки фахівців дошкільної освіти у контексті розвитку їх творчого потенціалу під час навчання у магістратурі.The pedagogical conditions of the development of the creative potential of masters of preschool education in the process of professional training are singled out and analyzed in the article. Author selects such main organized pedagogical conditions of the development of the creative potential of masters of preschool education in the process of professional training as: scientific and methodical providing of creative activity of the students in the process of education; providing of the qualified creative support of the professional personal becoming and development of the student; organization of the creative educational environment; stimulation and activation of the self-determination and self-realization of students in the process of scientific-investigating and independent practical creative activity of students in the process of professional training. The conclusion is made in the article that the realization of named pedagogical conditions of the development of the creative potential of specialists in the area of preschool education will promote the effectiveness of the professional training of pedagogue.
The pedagogical conditions of the development of the creative potential of masters of preschool education in the process of professional training
Keywords: педагогічні умови; творчий потенціал; педагогічні умови розвитку творчого потенціалу магістрів дошкільної освіти; pedagogical conditions; creative potential; pedagogical conditions of the development of the creative potential of masters of preschool education